The Influence of Leadership Style and Work Motivation on Employee Performance at The Office of The Department of Population and Civil Registration of Kepulauan Selayar District - Muh Arsandi; Romansyah Sahabuddin; Abdi Akbar; Burhanuddin; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
This aim is to determine the influence of leadership style and work motivation on employee performance at the Selayar Islands Regency Population and Civil Registration Office. The population in this study were all employees of the Office of the Population and Civil Registration Office of the Selayar Islands Regency, totaling 67 employees. The data used are primary data and secondary data obtained using a questionnaire distribution technique. This study uses a quantitative approach and is analyzed using the Multiple Linear Regression Analysis Method using SPSS 25 to prove three hypotheses. The results of this study prove that the Leadership Style variable has a significant effect on Employee Performance with a t count > t table and a sig value of. Work Motivation Variable has a significant effect on Employee Performance with a calculated value of t count > t table and a sig value of. Based on the results of this study, it is also known that the variables of Leadership Style and Work Motivation simultaneously or simultaneously have a significant effect on the dependent variable, namely Employee Performance at the Selayar Archipelago Regency Population and Civil Registration Office.